2022
DOI: 10.3390/su14137960
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Micro-Mobility Solutions for Improving Environmental Sustainability: Comparison among Transportation Systems in Urban Contexts

Abstract: Sustainable transport frameworks are gaining attention within national and international transportation policies, given the key role that decarbonisation plays in making urban environments people-friendly. Within this context, several shared services and micro-mobility options are being developed, especially as first/last mile facilities, further increasing public transport coverage levels. We present an overview of the environmental impacts of different transport modes and compare them from different perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…She shared, "sa pamasahe nakakabawas… kasi magkano lang naman ang charge ng e-bike na makokonsumo mo sa isang araw, sabi nila eighteen pesos… sabi nila… pero siguro ganun nga… medyo makaka-less ka ng pamasahe sa e-bike" Compared to traditional modes of transportation that rely on gasoline and other fossil fuel, electric bikes provide financial benefits and advantages to its users. According to D'Acierno et al (2022) [15] the use of micro-mobility solutions, such as electric bikes, can enhance environmental sustainability and provide cost-effective alternatives for traditional transportation systems in urban settings. Additionally, research has demonstrated that electric bikes offer a more cost-effective alternative for motorized modes of transportation than traditional, unaided bikes (Kwiatkowski et al, 2021) [26] .…”
Section: "Ah Instead Na Mag Commute Kami Magbayad Kami Ng Tricycle Or...mentioning
confidence: 99%
“…She shared, "sa pamasahe nakakabawas… kasi magkano lang naman ang charge ng e-bike na makokonsumo mo sa isang araw, sabi nila eighteen pesos… sabi nila… pero siguro ganun nga… medyo makaka-less ka ng pamasahe sa e-bike" Compared to traditional modes of transportation that rely on gasoline and other fossil fuel, electric bikes provide financial benefits and advantages to its users. According to D'Acierno et al (2022) [15] the use of micro-mobility solutions, such as electric bikes, can enhance environmental sustainability and provide cost-effective alternatives for traditional transportation systems in urban settings. Additionally, research has demonstrated that electric bikes offer a more cost-effective alternative for motorized modes of transportation than traditional, unaided bikes (Kwiatkowski et al, 2021) [26] .…”
Section: "Ah Instead Na Mag Commute Kami Magbayad Kami Ng Tricycle Or...mentioning
confidence: 99%
“…They also have broader impacts on fuel efficiency and carbon emissions. A recent study has shown that E-scooter has better emission and operation costs than internal combustion cars, electric cars, and even public electrical buses [11]. The micro-mobilities are also a good fit for modern and future society because of their health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental gains are the roots that vary in economic setup by means of CO 2 emissions and the ultimate costs of technologies like blockchain (Centobelli et al, 2021 ; D'Acierno et al, 2022 ). As mentioned above, Germany not only promoted the economic growth of the European Union but also played a crucial role in promoting the development of global science and technology innovation (Thomas, 2017 ; Zhou, 2020 ).…”
Section: Introductionmentioning
confidence: 99%